Avaliação do efeito desinfetante do cloro em fezes contendo o Vibrio cholerae - Patricia Procopio Pontes (1993)
This work had as the main objectives (i) the evaluation of the methodologies for the determination of residual chlorine in wastewaters, when applied to samples of high turbidity and elevate d concentrations of organic matter and (ii) the evaluation of the effects of chlorine dosagens upon the Vibrio cholerae. The first phase of the research consisted in the development of laboratory tests for evaluating the applicability of the DPD, oxi-reduc tion potential and amperometric titration methods in a the determination of residual chlorine in feces and raw wastewater samples. In the second phase, disinfection tests in pure cultures of vibrio cholerae and in feces samples were carried out, and the effects of chlorine dosages, contact time and sample mixing were evaluated. The results indicated a good correlation among the three methods, with the amperometric titration one being more accurate and less subject to interferences, although it was confirmed that all three methods can be applied in the determination of residual chlorine in feces and raw wastewater samples. In relation to the disinfection tests, the results for the feces sample indicated that chlorine dosages of around 1500 mg/ l were sufficie nt for the elimination of fecal coliforms, (independently of the contact time and the applied mix ing). For the disinfection tests of pure cultures of Vibrio cholerae, the necessary chlorine dosages were around 600 mg/ l. In both samples, the contact time and mixing variables did not significantly affect the disinfection process.